2013
DOI: 10.1182/blood-2012-01-403857
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated missense mutations in the EVH1 domain disrupt intrinsic WASp function causing dysregulated actin dynamics and impaired dendritic cell migration

Abstract: IntroductionWiskott Aldrich syndrome (WAS) is a primary immunodeficiency characterized by a broad immune defect, thrombocytopenia, severe eczema, and an increased susceptibility to both autoimmunity and hematologic malignancy. 1 The disease is caused by mutations in the gene encoding the WAS protein (WASp), a key regulator of the actin cytoskeleton in hematopoietic cells. 2,3 Cytosolic WASp exists in an autoinhibited conformation promoted by constitutive binding of the EVH1 domain to WASp Interacting Protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
(94 reference statements)
3
10
0
Order By: Relevance
“…One possible pathway is masking of WASp ubiquitylation sites by WIP. In support of this mechanism, we and others recently showed that WH1deleted WASp mutants are highly resistant to degradation (40,104). These truncated forms of WASp do not bind WIP but are still protected from degradation due to the absence of ubiquitylation sites.…”
Section: The Molecular Mechanism Of Wasp Downregulation Is Uncoveredmentioning
confidence: 71%
See 2 more Smart Citations
“…One possible pathway is masking of WASp ubiquitylation sites by WIP. In support of this mechanism, we and others recently showed that WH1deleted WASp mutants are highly resistant to degradation (40,104). These truncated forms of WASp do not bind WIP but are still protected from degradation due to the absence of ubiquitylation sites.…”
Section: The Molecular Mechanism Of Wasp Downregulation Is Uncoveredmentioning
confidence: 71%
“…Both WASp and N-WASp have an N-terminal WH1 domain that serves as the binding region for the WASpinteracting protein (WIP) (38). Through this constitutive interaction, WIP controls WASp activation and localization (39)(40)(41) and most importantly protects WASp from degradation (39,42). In T cells, the WH1 domain was also identified as a binding site for the Src family kinase Fyn (43), a kinase which is known to support the activity of WASp in T cells by phosphorylating its tyrosine 291 (24).…”
Section: Wasp Family Npfs: Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations associated with XLT tend to cluster in exons 2-4 (within the EVH1 domain) and are usually missense mutations predicted to interfere with WIP binding to WASp [69][70][71][72]. The reduced affinity for WIP has been demonstrated to result in an increased susceptibility to degradation of the mutated WASp protein [16,73]. Mutations causing classical WAS are more evenly distributed throughout the whole WAS gene; however, they are more likely to be deletion, nonsense or premature termination causing mutations.…”
Section: Genetic Testingmentioning
confidence: 99%
“…A total of 69% of these patients had missense mutations, the majority of which were within the WASp EVH1 domain. Increasing evidence suggests that WASp-WIP interaction has a specific role in WASp function, beyond simply protecting WASp from degradation [31,73,132]. As the majority of XLT mutations (those in the EVH1 domain) are predicted to interfere with WIP binding to WASp, this functional defect may explain the immune dysregulation seen in patients expressing reduced, but not absent levels of WASp.…”
Section: Management Of Xlt and Novel Therapiesmentioning
confidence: 99%